تأثير الأزمات والكوارث الطبيعية على السلوكيات والذهنيات بمجتمع الغرب الإسلامي - جعطوط عادل; قويسم محمد (University of Eloued جامعة الوادي, 2024)
This study deals with the impact of crises and natural disasters on behaviors and mentalities in the society of Islamic West, as it sheds light on some emerging perceptions, which were entrenched in the thought of that society over time, thus forming a mental structure that contradicts morals and constants, as some members of that society have become believers in magic and astrology and connected them The matter is the extent of sanctifying the practitioners of these phenomena, in addition to some other effects such as the looting of property and money, which in turn led to the phenomenon of fear and insecurity. Despite all of this, the vast majority of society preserved the spirit of solidarity and synergy among most of its elements, especially at the level of sultans and sufimen who worked to alleviate pain and suffering through their material and moral contribution. الملخص تعالج هذه الدراسة تأثير الأزمات والكوارث الطبيعية على السلوكيات والذهنيات بمجتمع الغرب الإسلامي، حيث سلطنا الضوء على بعض التصورات المستجدة، التي ترسخت في فكر ذلك المجتمع عبر الزمن، مشّكِلة بذلك بنية ذهنية منافية للأخلاقيات والثوابت، حيث أصبح بعض أفراد ذلك المجتمع يؤمنون بالسحر والتنجيم ووصل بهم الأمر حدّ تقديس ممارسي هذه الظواهر، إضافة إلى بعض التأثيرات الأخرى كنهب الممتلكات والأموال والتي أدت بدورها إلى ظاهرة الخوف وانعدام الأمن. وبالرغم من ذلك كله فإن السواد الأعظم من المجتمع حافظ على روح التكافل والتآزر بين أغلب عناصره، خاصة على مستوى السلاطين والمتصوفة الذين عملوا على تخفيف الآلام والأوجاع من خلال مساهمتهم المادية والمعنوية.
خلال القرنين (6ه-7ه)
Keywords: الكوارث الطبيعية; الذهنيات; السلوكيات; السحر; التضامن; natural disasters; mentalities; behaviors; Magic; Solidarity